It’s a big, BAD World- the UK picture of Big and Administrative Data: IJPDS (2017) Issue 1, Vol 1:230 Proceedings of the IPDLN Conference (August 2016) - Webb, Joanne (International Journal of Population Data Science, 2017)
ABSTRACT Background & Aims The Economic and Social Research Council (ESRC) have established a three strand programme to encourage the use of Administrative and Big Data in research. The first strand funded the Administrative Data Network, a UK-wide partnership between universities, government bodies, national statistics authorities and the wider research community. www.adrn.ac.uk. The Network facilitates secure research access to linked, de-identified administrative data to enable real-world analysis that can benefit society. The second strand covers the Big Data Centres: the Business and Local Government Data Centre, the Urban Big Data Centre and the Consumer Data Research Centre. These concentrate on making data routinely collected by business and local government organisations accessible for academics in order to undertake research in the social sciences. The third strand enables partnerships between academic institutions and citizen and voluntary sector organisations, to establish or build on relationships between academic researchers and civil society organisations. The aim is to demonstrate the value of improved data infrastructure, enabling collection and analysis of data which is of interest to civil society organisations and empowering the sector to better use its own data. All three strands aim to enable research in social sciences while safeguarding individuals’ identities. Working in a diverse changing landscape brings its own challenges and possibilities. The University of Essex hosts the Administrative Data Service of the ADRN, the Business and Local Government Data Centre and the Human Rights, Big Data and Technology Project. The challenge is to describe the boundaries, overlaps and synergies in the landscape. This paper will review the UK network of these partnerships, a description of some of the challenges of taking part in such a diverse growing landscape and some of the benefits to researchers and society.